Avaliação da sorção e solubilidade de água em cimentos de ionômero de vidro com e sem agente de proteção - Gomes, Camila de Siqueira (2021)
The aim of this study was to evaluate the effect of a surface coating agents on the sorption and water solubility of glass ionomer cements (GIC). Four materials were selected according to type/mode of presentation: Encapsulated resin-modified GIC (Riva Light Cure - RLC); Powder/liquid RM-GIC (Vitremer – VTM); Encapsulated conventional GIC (Equia Forte - EQF) and powder/liquid conventional GIC (Fuji IX Gold Label – FJIX). Twenty samples of each material were made, 10 with protection and 10 without surface protection. The Equia Forte Coat was the surface coating agents used. The samples were placed in desiccators, transferred to an oven at 37ºC and left to rest for 5 days. These were then weighed (m1) at 24-hour intervals. The thickness and diameter of the specimens were measured using a digital caliper to calculate their volume (V) in mm³. New weightings were performed (m2) at 1-hour intervals in the first 8 hours, at 24-hour intervals in the first 7 days and after 14 and 28 days. After 28 days of storage, the samples were dried in desiccators containing silica gel at 37ºC and left to rest for 5 days (m3). The sorption and solubility data obtained were subjected to analysis of variance (two-way ANOVA, material and surface coating agents) and Tukey test (α=0.05). For water sorption, there was a significant difference only for the material factor (p<0.05), VTM  EQF  RLC > FJIX. The conventional GIC FJIX showed the lowest sorption values, differing significantly from the other materials, regardless of the use of surface coating agents. There was no significant difference for the surface protection factor (p>0.05). For solubility there was no significant difference for the material factor, surface coating agents or material*surface coating agent interaction. It can be concluded that the use of surface coating agents did not influence the sorption and solubility values of the evaluated GIC and the conventional GIC FJIX showed lower sorption rates.